CORO6 Promotes Cell Growth and Invasion of Clear Cell Renal Cell Carcinoma via Activation of WNT Signaling - Wang, Xinjun; Xiao, Yiming; Li, Si; Yan, Zhijian; Luo, Guangcheng (Frontiers in Cell and Developmental Biology, 2021)
Renal cell carcinoma (RCC) constitutes the most lethal type of genitourinary cancer. Understanding of RCC tumor biology helps to identify novel targets and develop directed treatments for patients with this type of cancer. Analysis from both The Cancer Genome Atlas Kidney Renal Clear Cell Carcinoma dataset and our RCC samples demonstrated that the expression level of CORO6 was significantly higher in RCC patients than in normal kidney tissues, and its level was highly associated with tumor stage and grade. Importantly, CORO6 expression level was an independent predictor of tumor metastasis and overall survival in RCC patients. Our cell line data also confirmed that CORO6 knockdown could suppress RCC cell growth as well as cell migration and invasion. The depletion of CORO6 led to cell cycle arrest at the G0/G1 phase and caused cell apoptosis. Further, mechanistic dissection showed that CORO6 mediated RCC cell growth, and cell invasion relied on WNT signaling. Moreover, the in vivo data suggested that CORO6 knockdown indeed suppressed RCC tumor growth. Overall, our study defines the oncogenic role of CORO6 in RCC progression and provides a rationale for developing CORO6-targeted therapies for improved treatment of RCC patients.